Molecular dynamics-guided titanium platform with chitosan-assisted bacterial anchoring for sequential antibacterial and osteogenic functions - Jiaying Li; Junkai Hu; Jiamin Li; Weihan Zheng; Jiejie Wang; Tao Lin; Jiahao Pu; Tingting Chen; Mingrui Li; Hang Sang; Jianlin Shen; Lincong Luo; et al. (Chemical Engineering Journal, 2026)

Are there seasonal differences in supply and demand for blue-green space cooling in cities with hot summers and cold winters? – A case study from Tianjin, China - Fei Yang; Lei Wang; Lei Wang; Youhui Lin; Tianlin Zhang; Hongcheng Wang; Jiaying Li (Sustainable Cities and Society, 2026)

AMF and PGPR enhance Suaeda salsa phytoremediation of heavy metals-contaminated saline soils: Metabolic reprogramming and rhizosphere microbiome remodeling - Bingbing Jia; Peiran Guo; Jiaying Lin; Yunong Chen; Yiwen Xu; Wei Guo (Rhizosphere, 2026)

TMF: Temporal multi-modal fusion framework for estimating wheat yield from multi-source satellite and environmental data across the European Union - Zhixian Lin; Sheng Wang; Kaiyu Guan; Jiaying Zhang; Senthold Asseng; René Gislum; Jørgen Eivind Olesen; Klaus Butterbach-Bahl; Miroslav Trnka; Rui Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Zn2+-doped Mn-based layered oxide cathode with suppressed P3–O3 phase transition for high-efficiency potassium-ion batteries - Yingna Zhang; Chuye Pan; Zeyu Yuan; Liping Duan; Haowei Tang; Jiaying Liao; Yue Lin; Xiaosi Zhou (Science Bulletin, 2026)

Machine learning uncovers tidal DOM transformations and keystone molecules via FT-ICR MS and reactomics for estuarine nutrient cycling - Guosheng Zhao; Longfei Wang; Yi Li; Jiaying Chen; Lihua Niu; Li Lin (Journal of Environmental Sciences, 2026)

Intracranial Mitochondrial Microparticles Promote Cerebral Edema via Endothelial Injury in Stroke - Xiaoyan Du; Xintong Yu; Mengfei Wang; Ying Fu; Kunxin Lin; Jiaying Wu; Qianqian Lin; Wenlong Zhao; Yi Lin (Translational Stroke Research, 2026)

Nighttime growth in the green tide alga Ulva prolifera: metabolic basis and ecological implications - Han Xu; Mingzi Lin; Jiaying Bian; Dongyi Yang; Jianan Jiang; Shenyuan Liang; Hao Zhang; Wenrong Zhu; Nianjun Xu; Yahe Li (Journal of Applied Phycology, 2026)

Investigation of flavor formation mechanism of broad bean paste fermented by Bacillus amyloliquefaciens SCPC-RY2021 - Jiaying Cai; Ya Liu; Yue Xiang; Yilin Xie; Jie Tang; Chao Liu; Houqi Ning; Hongbin Lin (Food Research International, 2026)

East Asian monsoon and hydrodynamics regulate sinking and carbon export of zooplankton fecal pellets in the northern South China Sea - Luyang Wang; Zhifei Liu; Junyuan Cao; Baozhi Lin; Yulong Zhao; Jiaying Li; Xiaodong Zhang; Yuxin Huang; Jiarui Wang; Lina Cui (Marine Chemistry, 2026)

3D-printed porous titanium alloy scaffolds modified with composite hydrogel-loaded emodin liposomes for the treatment of periprosthetic joint infection - Jiamin Li; Jiaying Li; Junkai Hu; Tingting Chen; Tao Lin; Jiahao Pu; Lincong Luo; Wenhua Huang (Chemical Engineering Journal, 2026)

Influence of sample purity on landslide susceptibility mapping: a mutually exclusive stratified purity strategy based on the state-process consistency - Jiaying Zhu; Yuqian Yang; Shuangyun Peng; Zhiqiang Lin; Ziyi Zhu; Xianchun Pan; Xue Ding; Rong Jin (Bulletin of Engineering Geology and the Environment, 2026)
The quality and uncertainty of training samples are a critical bottleneck constraining the performance of machine learning in landslide susceptibility mapping (LSM). To address this, this study introduces a sample purity optimization framework based on state-process consistency (SPC). The framework utilizes two indices, SWCFD and CF-BE-HMD, combined with a mutually exclusive stratified purity strategy (MESPS), to systematically optimize the purity of the training samples. The framework was validated using data from Zhenxiong County, Yunnan Province, China. The results indicate that sample purity is the core variable influencing LSM model performance. The mutually exclusive sample group with the highest purity achieved AUC values of 0.92–0.93, markedly higher than those of other groups. High-purity landslide and non-landslide samples effectively suppressed the risk generalization effect caused by low-purity positive samples and overcame the risk conservatism problem induced by low-purity negative samples, resulting in clearer boundaries in the risk zonation. Therefore, only through bidirectional purification, which ensures that both positive and negative samples are highly representative, can these two extreme biases be maximally eliminated, leading to the generation of scientific, reliable, and balanced landslide susceptibility maps. This study offers a feasible solution to the sample quality bottleneck, providing a solid theoretical and empirical basis for shifting landslide modeling towards a quality-driven approach.

Restoration of saline-alkaline grasslands: microbiome transplantation promotes Leymus chinensis growth by reshaping multi-niche bacterial communities - Peiran Guo; Jiaying Lin; Bingbing Jia; Wei Guo; Frank Yonghong Li (Plant and Soil, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

A liquid reactive flame retardant strategy for CF/EP composites fabricated by vacuum infusion process - Mingming Yu; Jiaying Yao; Jiaxin Ma; Zhimin Gao; Dong Feng; Hao Huang; Ousheng Zhang; Wen Ye; Wang Xie; Lin Fang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Combined Microplastics and Cadmium Exposure Induces Persistent Gut Microbiota Dysbiosis in Pearl Oyster Pinctada fucata martensii - Luomin Huang; Yujing Lin; Lintao Liu; Qin Su; Jiaen Liu; Chuangye Yang; Jiaying Yao; Zixin Gao; Yuewen Deng (Fishes, 2026)
In marine aquaculture environments, microplastics (MPs) and cadmium (Cd) are widespread contaminants that may jointly affect host–microbe interactions. Here, we examined the combined effects of MPs (5 mg/L) and Cd (5 μg/L) on the intestinal microbial community of pearl oysters after a 48 h exposure, followed by a 5-day recovery period. Gut microbiota dynamics were characterized using 16S rRNA gene sequencing. Alpha diversity did not vary significantly, whereas beta diversity showed marked alterations in community composition among the different exposure treatments. LEfSe analysis revealed distinct microbial biomarkers and putative pathogens under each treatment: Sulfitobacter in the MPs-alone group; Vibrio and Candidatus_Megaira in the Cd-alone group; and Tenacibaculum, Roseibacillus, and Enterovibrio across different co-exposure and recovery groups. A brief recovery period partially decreased the abundance of certain pathogens (e.g., Vibrio), yet some taxa (e.g., Enterovibrio and Tenacibaculum) remained enriched. These results indicate that exposure to MPs and Cd, whether alone or in combination, disrupts gut microbial homeostasis in pearl oysters by reshaping community structure and promoting the proliferation of potential pathogens, with some disturbances persisting after exposure ceases. Generally, our findings will aid evaluation of the ecological risks of combined pollutants in marine aquaculture systems.

The attribution of subseasonal extreme precipitation in arid and semi-arid regions based on extended convergent cross mapping - Tingxing Chen; Attilio Castellarin; Yonghua Zhu; Haishen Lü; Andrea Magnini; Yinghao Fu; Yuan Li; Yu Lin; Zhenzhou Ding; Jiaying Liu (Journal of Hydrology, 2025)

Preparation of fish oil microcapsules for enhanced stability and controlled release via plug-and-play microfluidic chips - Peilan Xie; Zhenqian Tang; Ba Guan; Yimeng Tang; Qiyou Chen; Jiaying Ou; Kangmin Lin; Zhuo Jiang (Food and Bioproducts Processing, 2025)

Limited effects of control measures on soil recovery eight years after landslides in Northwestern China - Yiting Guo; Yinan Liu; Junyuan Zheng; Jiangxia She; Aopeng Xie; Jiaying Wang; Chenghua Shi; Jian Li; Yongming Lin (Ecological Engineering, 2025)

Deacetylation mediated non-covalent assembly for regulating sol-gel behavior of chitin-NaOH solution - Xinghuan Lin; Zhiqiang Liu; Ming Lei; Jiaying Xie; Hanji Chen; Shanshan Li; Bo Duan (Carbohydrate Polymers, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Establishment of a Novel Cell Line From the Fry of Grouper ( Epinephelus coioides ) for Fish Virus‐Host Interactions - Jiaying Zheng; Guojun Pan; Haotian Chen; Feifei Lin; Qiting Liu; Youhua Huang; Qiwei Qin; Xiaohong Huang (Journal of Fish Diseases, 2025)
Continuous cell lines are useful for virus research and diagnosis. Here, a novel cell line from grouper fry (Ec‐Fry) has been developed and its sensitivity to fish viruses was investigated. Mitochondrial 18S rRNA gene sequence analysis conducted after 80 generations of Ec‐Fry cells verified that Ec‐Fry cells originated from Epinephelus coioides . Ec‐Fry cells, mainly composed of epithelioid cells, exhibited the fastest growth with 15% and 20% FBS at 28°C, but also grew well with 5% FBS. Chromosome analysis showed that the number of type chromosomes was 48. After pEGFP‐N3 transfection, green fluorescence was observed in Ec‐Fry cells under a fluorescence microscope. Red‐spotted grouper nervous necrosis virus (RGNNV) and Singapore grouper iridovirus (SGIV) were able to propagate in Ec‐Fry cells, evidenced by the obvious cytopathic effect (CPE) progression and increased production of viral proteins with the infection time. Moreover, numerous viral particles were observed in SGIV‐ and RGNNV‐infected cells, suggesting that the infection model in Ec‐Fry could be used to investigate the viral pathogenesis. Moreover, the expression levels of pro‐inflammatory cytokines and interferon response‐related genes were significantly elevated during SGIV or RGNNV infection in Ec‐Fry cells, indicating that this infection model could also be used to explore the host immune response against fish virus infection. In addition, higher virus yields could be obtained in infected Ec‐Fry cells which were cultured with FBS at a low concentration, suggesting that Ec‐Fry cells were suitable for vaccine preparation in the future. Together, our findings provided a novel cell line from marine fish for virus isolation and host‐virus interactions.

HDAC3 Epigenetic Suppression by Electroacupuncture Restores AMPA Receptor Function and Synaptic Plasticity in Alzheimer’s Disease Models - Hongzhu Li; Bing Deng; Mucan Lin; Lanfeng Lai; Jiaying Zhao; Yuemei Li (NeuroMolecular Medicine, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

Grouper interleukin 15-like acts as a cytokine adjuvant in grouper iridovirus subunit vaccine - Jiaying Zheng; Haotian Chen; Qiting Liu; Feifei Lin; Xixi Guo; Xiaohong Huang; Qiwei Qin; Youhua Huang (Fish & Shellfish Immunology, 2025)

Core microbiome and microbial community characteristics of three ecological niches contribute to the growth of Leymus chinensis - Peiran Guo; Bingbing Jia; Jiaying Lin; Chengyan Lu; Tai Liu; Baihui Hao; Yiwen Xv; Qian Wang; Yvnong Chen; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

Water flow-driven high piezo-photocatalytic efficacy in superthin and densely porous GO-TiO2/PVDF-HFP composite film for ROS generation - Jialin Zhuang; Yechen Wang; Liping Lin; Jiaying Xiao; Jiahui Cai; Yingmo Hu; Qi An (Chemical Engineering Journal, 2025)

A Kinetic Study on the Accumulation of No.0 Fuel Oil and Pinghu Crude Oil Water-Accommodated Fraction in Exopalaemon carinicauda - Lei Li; Yiyun Zhang; Li Wei; Aijia Lin; Jiaying Cai; Zengqiao Wei; Qingyuan Wu; Junxiang Niu; Yanming Sui; Mei Jiang (Fishes, 2025)
The kinetic parameters of No.0 fuel oil and Pinghu crude oil water-accommodated fractions (WAFs) during accumulation and elimination in Exopalaemon carinicauda were quantified using a semi-static two-compartment kinetic model. The accumulation phase data were analyzed via nonlinear regression to obtain kinetic parameters, yielding critical values including the uptake rate constant (k1), elimination rate constant (k2), bioconcentration factor (BCF), equilibrium body burden (CAmax), and biological half-life (B1/2). Modeling results demonstrated distinct kinetic parameters for the two oils. For No.0 fuel oil, the average values were k1 = 5.21; k2 = 0.1105; BCF = 48.98; CAmax = 2.95 mg/kg; and B1/2 = 6.40 days. For Pinghu crude oil, the averages were k1 = 10.25; k2 = 0.1044; BCF = 98.15; CAmax = 8.48 mg/kg; and B1/2 = 6.64 days. The uptake rate constant (k1) and BCF generally decreased with increasing petroleum hydrocarbon exposure concentrations in ambient seawater, while the elimination rate constant (k2) remained relatively constant across different concentrations. CAmax increased proportionally with the petroleum hydrocarbon exposure concentration. Goodness-of-fit tests confirmed that the petroleum hydrocarbon concentrations in the experimental data were well described by the semi-static two-compartment model. Throughout the testing period, the concentration of No.0 fuel oil in Exopalaemon carinicauda remained lower than that of Pinghu crude oil.

Dietary trehalose reduced liver glycogen accumulation and promoted protein deposition in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) fed a high-carbohydrate diet - Yi Xiao; Xingbo Su; Jiaying Xie; Huiwen Zhang; Qiming Huang; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Delivery of NK cells in an injectable dynamic hydrogel effectively remodels tumor microenvironment and inhibits post-surgery tumor recurrence - Jiaying Long; Yicong Zhang; Mengxing Zhang; Zhenkang Diao; Taotian Zhang; Hanming Zhang; Qing Lin; Tao Gong; Xun Sun; Zhirong Zhang; Shiqi Huang; Ling Zhang (Chemical Engineering Journal, 2025)

Arbuscular mycorrhizal fungi enhance Leymus chinensis resistance to salinity predominantly through regulating root endosphere bacteria - Peiran Guo; Yazhou Hou; Bingbing Jia; Yuchen Wang; Chengyan Lu; Run Wang; Jiaying Lin; Yanan Zhang; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

The Combined Effects of Cadmium and Microplastic Mixtures on the Digestion, Energy Metabolism, Oxidative Stress Regulation, Immune Function, and Metabolomes in the Pearl Oyster (Pinctada fucata martensii) - Jiaying Yao; Zixin Gao; Zhixiang Wang; Zhanbo Ge; Yujing Lin; Luomin Huang; Jiaen Liu; Heqi Zou; Chuangye Yang; Robert Mkuye; Yuewen Deng (Fishes, 2025)
The accumulation of cadmium (Cd) and microplastics (MPs) can have major deleterious effects on the health of marine ecosystems and organisms, including the pearl oyster Pinctada fucata martensii. Here, we characterized the effects of Cd and MPs on key biochemical parameters of P. f. martensii via an experiment with various treatments. Pearl oysters were exposed to either only Cd (5 or 50 μg/L), only MPs (5 mg/L), or both Cd and MPs for 2 d, and this was followed by a 5-day recovery period. Measurements of the activities of lipase, amylase, protease, T-ATPase, catalase, glutathione peroxidase, acid phosphatase, and alkaline phosphatase enzymes, as well as the malondialdehyde content in the hepatopancreas, were made at various time points during the experiment. Metabolomics analysis of the gills was also performed. Significant interactions between time and treatment on lipase, protease, and catalase activities were observed. However, no significant effect of time–treatment interactions on amylase and T-ATPase activities was observed. Enzyme activities varied among groups both during the exposure period (6 to 48 h) and the recovery period. The malondialdehyde content was also increased throughout the experiment. Pathway analysis indicated that the purine metabolism, glycerophospholipid metabolism, nucleotide metabolism, arachidonic acid metabolism, neuroactive ligand–receptor interaction, and linoleic acid metabolism pathways were the most commonly affected under different treatments. The findings of our study revealed the differential effects of exposure time and treatment on enzyme activities and metabolites and their respective pathways. Our findings enhance our understanding of the biochemical responses of the pearl oyster P. f. martensii to environmental stressors, particularly Cd and MPs.

Docosahexaenoic acid alleviated liver lipid deposition and health damage induced by cholesterol accumulation in hybrid grouper (Epinephelus fuscoguttatus ♀ × E. lanceolatus ♂) - Qiming Huang; Huiwen Zhang; Xingbo Su; Yi Xiao; Jiaying Xie; Douglas R. Tocher; Fan Lin; Cuiying Chen; Shuqi Wang; Ruixin Li (Aquaculture, 2025)

Zooplankton fecal pellet flux and carbon export: The South China Sea record and its global comparison - Jiaying Li; Zhifei Liu; Baozhi Lin; Yulong Zhao; Xiaodong Zhang; Junyuan Cao; Jingwen Zhang; Hongzhe Song (Global and Planetary Change, 2025)

Optical study on the auto-ignition and knocking behaviors of ammonia/PODE RCCI mode - Ren Zhang; Lin Chen; Jinguang Li; Haiqiao Wei; Wei Li; Jiaying Pan (Fuel, 2025)

Synergy effect of nozzle structure and pre-chamber reactivity on the combustion characteristics of ammonia engines - Wenkai Zhao; Jiaying Pan; Haiqiao Wei; Lin Chen (Fuel, 2025)

Biological Traits of Spodoptera litura (Fabricius) in Response to Joint Application of Beauveria bassiana (Balsamo)Vuillemin and Emamectin Benzoate - Jiaying Li; Qingsong Cheng; Lin Chen; Kai Teng; Weiai Zeng; Hailin Cai; Shen Zhang; Zhipeng Xiao; Shaolong Wu; Bin Hu; Zhenxing Zhao; Hongwu Yang; et al. (Journal of Crop Health, 2025)

Thermodynamic mechanism of silica dosage and temperature on phase composition of well cement at high temperature and its impact on macro-properties - Huiting Liu; Tong Li; Jiaying Zhang; Pu Xu; Xiujian Xia; Yongjin Yu; Lin Liu; Huisu Chen (Applied Geochemistry, 2025)

Establishment of human minor salivary gland organoids in laminin-GelMA hydrogel from healthy individuals and Sjögren’s disease patients - Enhang Lu; Jiaying Qian; Wei Liang; Haibo Xiang; Pengbing Ding; Mengying Jin; Zhiyu Lin; Yujie Chen; Zheng Wang; Xin Huang; Zhixuan Sun; Bolin Pan; et al. (Chemical Engineering Journal, 2025)

Maternal exposure to ambient particulate matter on the growth of twin fetuses after in vitro fertilization - Jing Lin; Yang Shen; Fenglu Wu; Qianqian Zhu; Jialyu Huang; Jing Cai; Jiaying Lin (Science of The Total Environment, 2024)

A comparative study on NH3/H2 and NH3/CH3OH combustion and emission in an optical SI engine - Ren Zhang; Gequn Shu; Hua Zhao; Lin Chen; Haiqiao Wei; Jiaying Pan (Fuel, 2024)

Modulation of energy barrier of reaction steps over S-doped Ni(OH)2/Cu composites to achieve high-performance urea electrolysis catalysts - Xiaoyan Fan; Zhoujun Fu; Jiaying Lin; Bin He; Jing Zhang; Enlai Hu; Zhongwei Chen (Chemical Engineering Journal, 2024)

Temporal and vertical variations in carbon flux and export of zooplankton fecal pellets in the western South China Sea - Junyuan Cao; Zhifei Liu; Baozhi Lin; Yulong Zhao; Jiaying Li; Hanxiao Wang; Xiaodong Zhang; Jingwen Zhang; Hongzhe Song (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Changes in Sea Level along the South China Sea Coast Based on the Homogenized Tide Gauge Data - Yan Li; Lin Mu; Dawei You; Jiaying Wang; Qianru Niu; Xiaomei Liao (Journal of Marine Science and Engineering, 2024)
To estimate the changes in the annual mean sea level (MSL) and extreme sea levels (ESLs), the largest collection of tide gauge records from 10 tidal stations along the northern coast of the South China Sea (SCS) were analyzed in this study. Here, all the tide gauge records had been homogenized by a two-step process involving the detection of inhomogeneities, that is, breakpoints caused by non-climatic changes and the application of the adjustment. The study’s conclusions, based on the homogenized tide gauge records, can be summarized as follows: The instrument change and station relocation are the main causes for the identified inhomogeneities. From 1989 to 2018, the sea level along the SCS was at an average rate of 4.0 mm per year, as measured by the homogenized tide gauges. The ESLs from the nine tidal stations rose notably with interannual fluctuations, except for the XSA station. Additionally, the ESLs exhibited substantial decadal variations. The ESLs rose along the northern coast of the SCS and were accelerated at most stations throughout the whole study period, especially after the 1980s. There were significant positive correlations between the ESL and the annual MSL at most tide gauges. The MSL’s changes, especially long-term changes, play an important role in the change in ESLs.

Competitive enrichment of comammox Nitrospira in floccular sludge - Jiaying Hou; Ying Zhu; Jinzhong Liu; Limin Lin; Min Zheng; Linyan Yang; Wei Wei; Bing-Jie Ni; Xueming Chen (Water Research, 2024)

Phosphorylated hollow carbon-based material derived from ZIF-8 and its U(VI) adsorptive performance - Youqun Wang; Weiqian Cai; Lingshan Xiong; Jiaying Pei; Zhibin Zhang; Lin Xu; Yunhai Liu; Xiaohong Cao (Environmental Science and Pollution Research, 2024)

Risk assessment of terrestrial protected areas to extreme wind hazards: A case study in Queensland, Australia - Jinda Qi; Bao-Jie He; Yue Cao; Jiaying Dong; Ervine Shengwei Lin (Landscape and Urban Planning, 2023)

Fatigue Life Assessment in the Typical Structure of Large Container Vessels Based on Fracture Mechanics - Jinfeng Liu; Guoqing Feng; Jiaying Wang; Huilong Ren; Wei Song; Panpan Lin (Journal of Marine Science and Engineering, 2023)
Welding defects are known to cause crack propagation and reduce structural fatigue performance. Based on the Paris theory of fracture mechanics, research is conducted on evaluation methods for analyzing fatigue crack propagation by adopting random loads with long-term distribution that follows the Weibull distribution for the stress ranges of fatigue loads. This approach is combined with the corrective stress intensity factor (SIF) equation and the method for calculating the reference stress and failure criterion. A large container ship is selected for a simulation, and fatigue crack propagation analysis is conducted on typical critical locations. A detailed comparison of the forecasted fatigue life is carried out between fracture mechanics theory and the S-N curve. The results indicate that the fatigue life values obtained using the two methods are of the same magnitude. In general, for the welded structure, the fatigue life value obtained via the fracture mechanics method is shorter than that obtained via the S-N curve method, while, for the free edge of the structure and the unwelded structure, the predicted fatigue life value is closer than that predicted via the S-N curve method. Moreover, the influence of initial crack defects on the fatigue life is investigated, and the results show that the depth of the initial crack will greatly affect the fatigue life of the target ship in typical locations, but the influence of the shape ratio on the fatigue life is limited. Therefore, in the actual ship construction process, controlling the initial crack depth of components is effective for limiting crack propagation and improving fatigue life. The above conclusions and suggestions can serve as a reference for the structural design and fatigue life evaluation of large container ships.

Association of mitochondrial DNA variation with high myopia in a Han Chinese population - Shilai Xing; Siyi Jiang; Siyu Wang; Peng Lin; Haojun Sun; Hui Peng; Jiaying Yang; Hengte Kong; Sheng Wang; Qingshi Bai; Ruowen Qiu; Wei Dai; et al. (Molecular Genetics and Genomics, 2023)
High myopia (HM), which is characterized by oxidative stress, is one of the leading causes of visual impairment and blindness across the world. Family and population genetic studies have uncovered nuclear-genome variants in proteins functioned in the mitochondria. However, whether mitochondrial DNA mutations are involved in HM remains unexplored. Here, we performed the first large-scale whole-mitochondrial genome study in 9613 HM cases and 9606 control subjects of Han Chinese ancestry for identifying HM-associated mitochondrial variants. The single-variant association analysis identified nine novel genetic variants associated with HM reaching the entire mitochondrial wide significance level, including rs370378529 in ND2 with an odds ratio (OR) of 5.25. Interestingly, eight out of nine variants were predominantly located in related sub-haplogroups, i.e. m.5261G > A in B4b1c, m.12280A > G in G2a4, m.7912G > A in D4a3b, m.94G > A in D4e1, m.14857 T > C in D4e3, m.14280A > G in D5a2, m.16272A > G in G2a4, m.8718A > G in M71 and F1a3, indicating that the sub-haplogroup background can increase the susceptible risk for high myopia. The polygenic risk score analysis of the target and validation cohorts indicated a high accuracy for predicting HM with mtDNA variants (AUC = 0.641). Cumulatively, our findings highlight the critical roles of mitochondrial variants in untangling the genetic etiology of HM.

A 3D modeling study of effects of heterogeneity on system responses in methane hydrate reservoirs with horizontal well depressurization - Xuyang Guo; Yan Jin; Jingyu Zi; Jiaying Lin; Bolong Zhu (Gas Science and Engineering, 2023)

Estimating the thermal conductivity of granular soils based on a simplified homogenization method - Jinzhi Lin; Xiusong Shi; Yiwen Zeng; Yanhua Nie; Jiaying Liu (Cold Regions Science and Technology, 2023)

Mechanism, design and application of fluorescent recognition based on metal organic frameworks in pollutant detection - Borui Jie; Huidong Lin; Yixuan Zhai; Jiaying Ye; Deyu Zhang; Yifan Xie; Xiaodong Zhang; Yiqiong Yang (Chemical Engineering Journal, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Numerical Investigation of Depressurization through Horizontal Wells in Methane-Hydrate-Bearing Sediments Considering Sand Production - Xuyang Guo; Yan Jin; Jingyu Zi; Jiaying Lin; Bolong Zhu; Qian Wen; Qi Jing (Journal of Marine Science and Engineering, 2022)
Sand production has been identified as a key reason limiting sustained and commercial gas production in methane-hydrate-bearing sediments. Production tests in Canada and Japan were terminated partially because of excessive sand production in pilot wells. It is meaningful to carry out numerical investigations and sensitivity analyses to improve the understanding of sand production mechanisms during the exploitation of methane hydrates. This study introduces a numerical model to describe the coupled thermal–hydraulic–mechanical–chemical responses and sand production patterns during horizontal well depressurization in methane-hydrate-bearing sediments. The model is benchmarked with a variety of methane hydrate reservoir simulators. Results show that the spatial and temporal evolution patterns of multi-physical fields are different and the hydromechanical evolutions are the fastest. Gas production and sand production rates are oscillatory in the early stages and long-term rates become stable. Gas production is sensitive to rock physical and operational parameters and insensitive to rock mechanical properties such as cohesion. In contrast, sand production is sensitive to cohesion and insensitive to rock physical and operational parameters. Although cohesion does not directly affect gas productivity, gas productivity can be impaired if excessive sand production impedes production operations. This study provides insights into the sand production mechanism and quantifies how relevant parameters affect sand production during the depressurization in methane-hydrate-bearing sediments.

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Landscape planning of stone mine park under the concept of ecological environment restoration - Jiaying Li; Baogang Lin (Arabian Journal of Geosciences, 2022)

Genome-Wide Characterization and Analysis of Expression of the Histone Gene Family in Razor Clam, Sinonovacula constricta - Jiaying Lian; Liyuan Lv; Hanhan Yao; Zhihua Lin; Yinghui Dong (Fishes, 2021)
The Chinese razor clam (Sinonovacula constricta), a bivalve species widely distributed in estuaries and mudflats, is often exposed to extreme environmental and microbial stresses. Histones are fundamental components of chromatin and play an important role in innate immunity, as demonstrated by its antimicrobial activities in clams. However, little attention has been paid to histones in bivalves. To fill this gap, we investigated the genomic distribution, structural characteristics, conserved motifs, and phylogenetic relationships of histones in S. constricta. A total of 114 histone genes were detected in the S. constricta genome, which were divided into 25 types in phylogenetic analysis. Among them, partial histones exhibited a tissue-dependent expression pattern, indicating that they may be involved in sustaining the homeostasis of organs/tissues in adult S. constricta. Furthermore, mRNA expression of certain histones changed significantly in S. constricta when infected with Vibrio parahaemolyticus, suggesting that histones play a role in the immune defense of S. constricta. All together, this study on histone genes in S. constricta not only greatly expands our knowledge of histone function in the clam, but also histone evolution in molluscs.

The involvement of α‐proteobacteria Phenylobacterium in maintaining the dominance of toxic Microcystis blooms in Lake Taihu, China - Jun Zuo; Lili Hu; Wei Shen; Jiaying Zeng; Lin Li; Lirong Song; Nanqin Gan (Environmental Microbiology, 2021)
Summary Lake Taihu in China has suffered serious harmful cyanobacterial blooms for decades. The algal blooms threaten the ecological sustainability, drinking water safety, and human health. Although the roles of abiotic factors (such as water temperature and nutrient loading) in promoting Microcystis blooms have been well studied, the importance of biotic factors (e.g. bacterial community) in promoting and meditating Microcystis blooms remains unclear. In this study, we investigated the ecological dynamics of bacterial community, the ratio of toxic Microcystis , as well as microcystin in Lake Taihu. High‐throughput 16S rRNA sequencing and principal component analysis (PCA) revealed that the bacteria community compositions (BCCs) clustered into three groups, the partitioning of which corresponded to that of groups according to the toxic profiles (the ratio of toxic Microcystis to total Microcystis , and the microcystin concentrations) of the samples. Further Spearman's correlation network showed that the α‐proteobacteria Phenylobacterium strongly positively correlated with the toxic profiles. Subsequent laboratory chemostats experiments demonstrated that three Phenylobacterium strains promoted the dominance of the toxic Microcystis aeruginosa PCC7806 when co‐culturing with the non‐toxic PCC7806 mcyB − mutant. Taken together, our data suggested that the α‐proteobacteria Phenylobacterium may play a vital role in the maintenance of toxic Microcystis dominance in Lake Taihu.

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord - Yunlong Xu; Yanjun Jiang; Lin Wang; Jiahua Huang; Junmao Wen; Hang Lv; Xiaoli Wu; Chaofan Wan; Chuanxin Yu; Wenjie Zhang; Jiaying Zhao; Yinqi Zhou; et al. (Neuroscience Bulletin, 2019)

Study on the nutritional value and ruminal degradation characteristics of fermented waste vinegar residue by N. sitophila - Ci Liu; Lin Zhang; Jiye Yang; Wenjia Zhang; Qianqian Wang; Jianxin Zhang; Jiaying Xin; Shuming Chen (Tropical Animal Health and Production, 2019)

Endophytic Diaporthe from Southeast China are genetically diverse based on multi-locus phylogeny analyses - Jiaying Wang; Xihui Xu; Lijuan Mao; Jiaping Lao; Fucheng Lin; Zhilin Yuan; Chulong Zhang (World Journal of Microbiology and Biotechnology, 2014)

Genetic diversity and positive selection analysis of classical swine fever virus isolates in south China - Haiyan Shen; Jingjing Pei; Jialin Bai; Mingqiu Zhao; Chunmei Ju; Lin Yi; Yanmei Kang; Xuetao Zhang; Lijun Chen; Yinguang Li; Jiaying Wang; Jinding Chen (Virus Genes, 2011)